Urban Vulnerability and Climate Change in Africa: A Multidisciplinary Approach - Pauleit, S (Springer, 2015)
Urbanisation and climate change are among the major challenges for sustainable development in Africa. The overall aim of this book is to present innovative approaches to vulnerability analysis and for enhancing the resilience of African cities against climate change-induced risks. Locally adapted IPCC climate change scenarios, which also consider possible changes in urban population, have been developed. Innovative strategies to land use and spatial planning are proposed that seek synergies between the adaptation to climate change and the need to solve social problems. Furthermore, the book explores the role of governance in successfully coping with climate-induced risks in urban areas. The book is unique in that it combines: a top-down perspective of climate change modeling with a bottom-up perspective of vulnerability assessment; quantitative approaches from engineering sciences and qualitative approaches of the social sciences; a novel multi-risk modeling methodology; and strategic approaches to urban and green infrastructure planning with neighborhood perspectives of adaptation.